Isolation, Purification and Characterization of Caprine Pancreatic Islets - Homayoun Hani, (2009)
Diabetes mellitus is a major late consequence of chronic pancreatitis. Diabetes mellitus type 1 or insulin-dependent diabetes mellitus (IDDM) is characterized by the failure of the pancreatic islets of Langerhans to synthesis or secrete insulin. The longterm complications of IDDM are major health problems, and in these diabetics exogenous insulin may not adequately regulate blood glucose homeostasis and thus fail to avert the late complications. In this case, transplantation of pancreatic islets is arguably the most logical approach to restoring metabolic homeostasis. The limited availability of human donors makes the search for alternative source of islet cells mandatory for future developments in pancreatic transplantation. The present study investigates the potential of goats as an alternative source of pancreatic islets. The objectives of the study were to optimize techniques for goat islet isolation and purification for culture establishment, and to perform functional, morphological and viability assessment of goat islets. Goat pancreatic tissues were collected within 15 min of slaughter, placed in Hanks balance salt solution (HBSS) and maintained at 4oC. Goat islets were obtained successfully using a collagenase-based digestion and isolation technique at an optimized pH of 7.2 to 7.4 and temperature of 37oC. Digested pancreatic islets were purified by Euro-Ficoll density gradients. Islet cell purity and viability were determined by dithizone and trypan blue staining, respectively. Islet clusters of different sizes were positively identified by both staining methods and it was observed that 90% of clusters were viable in the culture system. Following the static incubation, an in vitro insulin secretion assay was carried out by ELISA to determine the islets viability. The islets remained viable for 5 days in the culture system following regular media changes. Pancreatic tissues were fixed in Bouin’s solution stained with hematoxylin-eosin (H&E) and immunohistochemistry (IHC) stains and examined microscopically to estimate the islet mass and determine insulin secretion ability. Under the light microscope, there were minimal connective tissue cells separating the islets from the surrounding exocrine component. The nuclei of islets cellswere uniform in size and surrounded by eosinophilic cytoplasm. Purified islets of Langerhans were fixed in a mixture of paraformaldehyde and glutaraldehyde solution for transmission (TEM) and scanning electron microscopic (SEM) examination. Under TEM, the caprine islet cell exhibited their characteristic secretory granules, which were of various sizes and electron opacity. The cells also showed characteristic abundance of rough endoplasmic reticulum (RER) and mitochondria. In b-cells, the rough endoplasmic reticulum was inconspicuous. The -cells are characterized by their peripheral location in the islet being larger and having electron-dense secretory granules. Based on morphological criterion, intermediate cells are shown to be present in both the endocrine and exocrine tissue of the normal pancreas of goats. Under SEM the size of the islet clusters was shown to range from 50 to 250 μm. Cells with secretory sacs on the surface could possibly be the isolated islet cells. The study had provided an optimized isolation and purification techniques for goat pancreatic islets to be further developed and used for xenotransplantation in diabetic animal models. The findings can lead to further research in identification and sequencing of insulin indicator genes, pancreatic hormones biomarkers and long-term cryopreservation of goat pancreatic islets.